Analisis Karakteristik Aerodinamis Turbin Angin Poros Horizontal Tiga Bilah - Hizkia Lukas Jeliasta Ginting; Maria F. Soetanto (INOVTEK - SERI MESIN, 2021)
This thesis is three bladed horizontal axis wind turbine simulation using airfoil LS-0417 and cylindrical profile combination. This horizontal axis wind turbine model will be designed by using Gambit software and then will be simulated by using Fluent software. In this thesis, hopefully this simulation can get the aerodynamic characteristic and flow pattern around the wind turbine on several variations of tip speed ratio.Keyword: Horizontal Axis Wind Turbine, Cylindrical and Airfoil LS-0417 Profile Blade Combination, Aerodynamic Characteristic